YouTube for EFL Students: Perceptions on Building Speaking Confidence - Musdayanti Musdayanti; Putu Wahyu Sudewi; Nurhaeni Nurhaeni (PT. Global Research Collaboration, 2024)
This study aimed to investigate students' perceptions of utilizing YouTube as a learning medium to foster their speaking confidence in English. Specifically, it explored students' views on YouTube's accessibility, usefulness, and practicality while examining its potential to enhance their confidence in speaking English. The researchers collected data through questionnaires and interviews with 10 second-grade students from SMAN 1 Tinambung. The findings revealed that students perceived YouTube as an accessible and user-friendly platform, aiding their comprehension and vocabulary expansion. Furthermore, they found it useful and motivating to practice proper English-speaking skills. Notably, students acknowledged YouTube's role in triggering their confidence to speak English, whether in front of a camera or in class settings. Peer feedback and comments were deemed valuable for augmenting knowledge and confidence. The questionnaire data indicated positive perceptions, with 80% acknowledging YouTube's accessibility, 82% recognizing its usefulness, 84% appreciating its practicality, and 72% reporting increased confidence levels. The interview data further corroborated these findings, with most students endorsing the continued integration of YouTube, as it facilitated their understanding of lesson materials and bolstered their confidence in spoken English. The study underscored YouTube's potential as an effective learning medium for developing EFL learners' speaking confidence.